Effects of Different Treatment Methods on the Clinical and Urodynamic State of Perimenopausal Women with Stress Urinary Incontinence - Lifen LIU; Ying ZHANG; Jingya GONG; Xin CHEN; Hongmei WU; Weipei ZHU (Tehran University of Medical Sciences, 2018)
Background: This study was designed to investigate the clinical effects of different treatment methods on stress urinary incontinence (SUI) in perimenopausal women, and to evaluate urodynamic characteristics. Methods: Seventy-two menopausal female patients with stress urinary incontinence were included in the Second Affiliated Hospital of Soochow University from January 2016 to July 2017. The cases were divided into 3 groups of 24 each, depending on the treatment received. Group A patients received treatment with electrical stimulation combined with biofeedback; those in group B received conventional pelvic floor muscle exercise therapy; and those in group C did not have any treatment. Relevant clinical parameters of urination were determined including pelvic floor muscle strengths, urine dynamics indexes and ICS quality of life survey scores; results were averaged in each group for comparisons among the three groups before and after the 60-day study period. Results: After treatment for 60 days, both group A and B patients displayed a clear improvement in their urinary incontinence, pelvic floor muscle strength, leakage times, frequency of urination, urine dynamics index and ICS scores (P<0.05), with group A showing the most improvement. Women in group C showed no significant difference before and after the 60-day study period (P>0.05). Conclusion: Both the method of electrical stimulation combined with biofeedback, and conventional pelvic floor muscle exercises could help perimenopausal women with stress urinary incontinence; however, electrical stimulation combined with biological feedback seems to bring about better clinical effects.